Nickel-Catalyzed Direct Addition of Diorganozinc Reagents to Phthalimides: Selective Formation of Gamma-Hydroxylactams - Dennis, Joseph M.; Calyore, Catherine M.; Sjoholm, Jessica S.; Lutz, J. Patrick; Gair, Joseph J.; Johnson, Jeffrey B. (Synlett, 2013)
The nickel-catalyzed addition of diorganozinc reagents to phthalimides proceeds with excellent selectivity to provide 3-substituted-3-hydroxyisoindolin-1-one products. These 3-hydroxy-γ-lactams are produced cleanly in high yield with numerous examples of imide substitution and a broad range of diorganozinc reagents that are prepared and utilized without purification.
Keywords: imide; catalysis; lactams; organometallic reagents; nickel